GCT-06. Management of a congenital intracranial teratoma: a case report and review of literature. (3rd June 2022) - Shatara, Margaret; Cantor, Evan; Ramos, Kristie N; Yu, Jonathan; Hassan, Ahmad; Shimony, Joshua S; Han, Peng Cheng; Meyer, Ashley; Ogle, Andrea; McHugh, Michele; Green, Tammy; Beck, Mary; et al.
Abstract: INTRODUCTION: Congenital intracranial teratomas (CITs) are rare tumors occurring in the first 60 days of life, often associated with dismal prognosis, posing challenges in both oncologic and surgical management. METHODS: We report a patient with a congenital mature teratoma diagnosed prenatally, who underwent successful surgical resection following neoadjuvant chemotherapy. We also performed an updated literature review on CIT outcomes. RESULTS: A newborn female, diagnosed prenatally with a complex midline intracranial echogenic mass, underwent postnatal brain MRI which demonstrated a supratentorial large complex enhancing mass with solid and cystic components, with associated obstructed hydrocephalus. Serum alpha-fetoprotein (AFP) and beta-human chorionic gonadotropin were normal for age. Tumor biopsy revealed mature teratoma. AFP obtained from cyst fluid during fenestration was significantly elevated at 8 weeks of life. Due to concerns for possible malignant transformation and in an attempt to alter tumor vascularity facilitating surgical resection, the patient received two cycles of neoadjuvant carboplatin and etoposide, followed by tumor resection without significant intraoperative bleeding. There was no evidence of immature components on final pathology. The patient remains without tumor recurrence, now 9 months, since surgical resection. Review of literature yielded 76 cases of CITs: eight patients with mature teratoma, of which six remained alive following tumor resection. Five patients with immature teratoma received chemotherapy prior to resection; three remained alive post-resection (follow-up range 3-20 years). DISCUSSION: CITs are typically associated with poor prognosis, with reported one-year survival of 7.2-12%. Surgical excision is the mainstay of treatment, often limited by intraoperative hemorrhage. Neoadjuvant chemotherapy has been employed as a successful strategy to reduce tumor volume and vascularity in a variety of pediatric brain tumors; more specifically, carboplatin and etoposide are utilized as neoadjuvant chemotherapy for non-germinomatous germ cell tumors to facilitate excision in older children. Their role in CITs requires further evaluation.